Constructivist Learning in Virtual Reality: Enhancing Classroom Engagement through VRLEs - Dreger, Kelly C. (Language, Literature and Education: Research Updates Vol. 2, 2025)
All across the nation’s educational institutions, creative strategies are developed that attempt to increase student recruitment and retention. These initiatives seek to engage and motivate in order to attract new students and assist existing students in progressing through their degree programs. Virtual Reality Learning Environments (VRLEs) are an innovative strategy to meet these goals. Some disciplines have been using VRLEs for student learning for several years (e.g., computer science, medicine, and engineering); however, the technology has not been used more broadly in others. This is changing due to the lower cost and widespread availability of the software and hardware required to use virtual reality; however, more research needs to be conducted to determine the overall barriers to VRLE implementation and the ways practical VRLEs can be linked to research and theory. A descriptive study was created to investigate, explore, and review the challenges of using VRLE. Results showed that challenges center around these areas: (a) costs, (b) space, (c) accessibility, (d) usability and training, and (e) cybersickness. A flexible and affordable VRLE can provide a solution to these challenges, particularly when framed within a constructivist lens. A seven-step model for constructive implementation of VRLEs is proposed as a result. VRLEs in the education setting are considered constructive when they include active learning, creation of meaning, individual exploration, open-ended interactions, creative contexts, critical thinking, reflection, documentation, comparison, and contrast. The proposed model would interest anyone who would like to know more about virtual reality and the implications it has for the classroom setting.